Price, Service Quality and Shipping Costs as Intervening Factors on Consumer Behavior To Determine Repeat Purchase Intentions on The Shopee Marketplace in Indonesia - Panjaitan, Mangasa; Butar-Butar, Hotlan (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
The purpose of this study is to determine the effect of price and service quality on consumer behavior to determine repurchase intentions at the Shopee marketplace in Indonesia through the variable shipping cost as an intervening factor. The research method used in this research is quantitative descriptive research method using data analysis, namely path analysis using PLS 3.0 software. Based on the results of the research analysis, the conclusion of this study is that partially the price and service quality variables affect the consumer behavior variable to determine repurchase intentions in the marketplace on the Shopee platform. Simultaneously, the price and service quality variables affect the consumer behavior variable to determine repurchase intentions in the marketplace on the Shopee platform through the shipping cost variable as an intervening factor. in the context of repeat purchase intentions from an Islamic perspective, businesses should focus on adhering to Islamic principles of fair pricing, ethical conduct, and transparency in pricing and shipping. The implications of this research will be very useful in optimizing Shopee business operations and providing better services to customers, with the hope of increasing repeat purchase intentions and strengthening Shopee's position in the e-commerce market in Indonesia.